2010
DOI: 10.1007/s13238-010-0019-9
|View full text |Cite
|
Sign up to set email alerts
|

MAPK signaling in inflammation-associated cancer development

Abstract: Mitogen-activated protein (MAP) kinases comprise a family of protein-serine/threonine kinases, which are highly conserved in protein structures from unicellular eukaryotic organisms to multicellular organisms, including mammals. These kinases, including ERKs, JNKs and p38s, are regulated by a phosphorelay cascade, with a prototype of three protein kinases that sequentially phosphorylate one another. MAPKs transduce extracellular signals into a variety of cellular processes, such as cell proliferation, survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
158
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(166 citation statements)
references
References 84 publications
4
158
0
4
Order By: Relevance
“…The transcription factors NF-κB and MAPKs are particularly important in colon cancer development (Danese and Mantovani, 2010;Huang et al, 2010). Activation of NF-κB contributes to the activation of innate immunity, inflammation, cell proliferation, and survival.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factors NF-κB and MAPKs are particularly important in colon cancer development (Danese and Mantovani, 2010;Huang et al, 2010). Activation of NF-κB contributes to the activation of innate immunity, inflammation, cell proliferation, and survival.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that overexpression of LTF downregulated the expression of p38, JNK2 and c-Jun in the SGC7901 cells. MAPKs transduce extracellular signals, promoting a variety of cellular processes, including cell proliferation, survival, death and differentiation (29). JNK and p38 MAPK signaling are associated with various types of cancer in humans and mice (30).…”
Section: Discussionmentioning
confidence: 99%
“…16,28,29 Prior to this study, aberrations in MAPK signaling have been linked to a variety of cancers but not to the pathogenesis of DLBCL tumors. 16,[30][31][32] Our specific findings include previously unknown activation of the GCK signaling pathway in DLBCL. We further demonstrate that GCK knockdown in DLBCL leads to decreased proliferation and cell death.…”
Section: Discussionmentioning
confidence: 80%